Justice Statistics: An Extended Look at Crime in the United States 2023 - Hertz Hattis, Shana (Bernan Press, 2023)
Justice Statistics: An Extended Look at Crime in the United States is a special edition of Crime in the United States. It brings together key reports that fall under this category. Topics covered include capital punishment, rape and sexual assault among college-age women, correctional populations, crime in the United States, hate crimes, probation, parole, human trafficking, and law enforcement officers killed and assaulted. Tables in this volume provide a comprehensive account of each of these subjects. Each section contains statistical tables and figures highlighting the data, as well as a brief summary of the report’s methodology and at-a-glance highlights of the most compelling information. This completely updated volume providesvaluableinformation compiled by the Department of Justice, including its subsidiaries, the Bureau of Justice Statistics and the Federal Bureau of Investigation.